Produção da uma galectina recombinante de anuros a partir da bioprospecção e mapeamento tecnológico das galectinas-9 - Rodrigues, Cássia Ferreira (2023)
Galectins are a family of animal lectins that have the ability to bind reversibly to carbohydrates with a high affinity for β-galactosides. They are expressed in different organisms and are involved in cell adhesion, tumor differentiation, apoptosis and have thus been the subject of technological product development. As few amphibian galectins have a primary structure or a solved three-dimensional structure, the structural elucidation of these lectins will make it possible to reveal their mechanisms of action within cells and evaluate their biotechnological potential. Thus, the aim of this work was to produce a recombinant galectin encoded in the anuran genome based on information obtained from molecular bioprospecting and a review of patents related to galectins. The galectin present in the secretion of the paratoid gland of Rhinella diptycha was partially purified using ion exchange chromatography and the fractions obtained from the chromatography were subjected to the hemagglutination test with rabbit erythrocytes and it was possible to identify the presence of the active galectin in one of the fractions. Using mass spectrometry, it was possible to obtain the primary structure of R. diptycha galectin, which is composed of 393 amino acid residues with a molecular mass of 51 kDa and a triple domain. Through a search for protein sequences similar to R. diptycha galectin in the National Center for Biotechnology Information (NCBI) database, B. bufo galectin-9 was found to be highly similar to R. diptycha galectin, which is why it was decided to produce it heterologously. Thus, two strains of Komagataella pastoris were transformed with the expression vector pPICZα(A) containing the gene encoding galectin, after codon optimization. Subsequently, the target protein was expressed through induction with methanol, and a molecule with a mass of 48 kDa was obtained, referring to recombinant galectin-9. Using the data available in the European Patent Office (EPO) and Cortellis Drug Discovery Intelligence (CDDI) databases, technological advances related to galectin-9 were mapped. In this survey, galectin-9 is related to various diseases, including several types of cancer, and has been used as a target for treatment or as a biomarker for cancer diagnosis. Therefore, galectin-9 with a triple secretion domain from R. diptycha, and recombinant galectin-9 from B. bufo are proteins from a family with demonstrated efficacy in technological prospecting, in terms of their anticancer activity, and will thus contribute to diagnosis or treatment in response to global demand.